The “Tale Of Gamelyn” Of The “Canterbury Tales”: An Annotated Edition. By Nila Vázquez. Lewiston: The Edwin Mellen Press, 2009. Pp. Vi, 466. - Thaisen, Jacob (Studia Anglica Posnaniensia, 2013)
Reviewed by Jacob Thaisen, University of Stavanger: The “Tale of Gamelyn” of the “Canterbury Tales”: An annotated edition. By Nila Vázquez. Lewiston: The Edwin Mellen Press, 2009. Pp. vi, 466.